Tanggung Jawab Notaris Werda Terhadap Hilangnya Minuta Akta - Caesar Faturahman Hadju (Officium Notarium, 2021)
This research raises the problems of first, how is the responsibility of the retired notary who has lost their minutes of the deed. Second, how is the legal protection for the parties who request for the copy of the minutes of the deed after the notary has retired. This is a normative legal research, using a statutory approach that is supported by interviewing source persons. This study concludes that first, when a notary retired, they must submit the notary protocol to another predecessor notary. If there is a problem with the loss and damage to the minutes of the deed before the retirement, the retired notary can be held civilly and criminally responsible. Second, there are no regulations governing legal protection for parties who lose their minutes of deed. There is also an alternative that the parties can seek, which is to make a new deed by mutual agreement to ensure legal certainty for the partiesKey Word: Notary, Retired Notary, ResponsibilityAbstrakPenelitian ini mengangkat permasalahan pertama, bagaimana tanggung jawab notaris yang telah werda atas hilangnya minuta akta. Kedua, bagaimana perlindungan hukum terhadap para pihak yang meminta salinan aktanya atas hilangnya minuta akta setelah notaris werda. Jenis penelitian dalam penelitian hukum ini adalah normatif, dengan menggunakan pendekatan perundang-undangan (statue approach) yang didukung dengan wawancara narasumber. Penelitian ini menyimpulkan, pertama, ketika notaris werda maka harus menyerahkan protokol notaris ke pada notaris lain. Jika terjadi permasalahan terhadap hilang dan rusaknya minuta akta sebelum werda maka notaris werda dapat dimintai pertanggungjawaban secara perdata dan pidana. Kedua, tidak ada peraturan yang mengatur tentang perlindungan hukum bagi para pihak yang kehilangan minuta aktanya. Ada pun yang dapat dilakukan para pihak yaitu membuat akta baru dengan kesepakatan bersama untuk menjamin kepastian hukum untuk para pihakKata Kunci: Notaris, Notaris Werda, Pertanggung-jawaban